2020
DOI: 10.7554/elife.56749
|View full text |Cite
|
Sign up to set email alerts
|

A powerful drug combination strategy targeting glutamine addiction for the treatment of human liver cancer

Abstract: The dependency of cancer cells on glutamine may be exploited therapeutically as a new strategy for treating cancers that lack druggable driver genes. Here we found that human liver cancer was dependent on extracellular glutamine. However, targeting glutamine addiction using the glutaminase inhibitor CB-839 as monotherapy had a very limited anticancer effect, even against the most glutamine addicted human liver cancer cells. Using a chemical library, we identified V-9302, a novel inhibitor of glutamine transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 42 publications
3
99
0
1
Order By: Relevance
“…Therefore, successful strategies targeting the role of glutamate in cancers have focused on restricting glutamine metabolism via glutaminase inhibition (132). Studies investigating the noncompetitive allosteric GLS1 inhibitor CB-839 have demonstrated that blocking glutamine metabolism has anticancer activity against triple-negative breast cancer, lung adenocarcinoma, chondrosarcoma, lymphomas, esophageal squamous cell carcinoma, and hepatocellular carcinoma (132)(133)(134)(135)(136)(137)(138). Currently, there are 12 ongoing clinical trials evaluating the CB-839 in patients with colorectal cancer (NCT02861300 and NCT03263429), myelodysplastic syndrome (NCT03047993), advanced stage non-small cell lung cancer (NCT04250545 and NCT03831932), diffuse astrocytoma (NCT03528642), ovarian cancer (NCT03944902), refractory multiple myeloma (NCT03798678), advanced or metastatic solid tumors ( N C T 0 3 9 6 5 8 4 5 ) , m e t a s t a t i c r e n a l c e l l c a r c i n o m a (NCT03428217), malignancies with NF1, KEAP1/NRF2, or STK11/LKB1 mutations (NCT03872427), and non-squamous non-small-cell lung cancer (NCT04265534).…”
Section: Restriction Of Glutamate or Glutamine Metabolism Via Inhibitors Of Glutaminase Are Effective Against Myelodysplastic Syndromementioning
confidence: 99%
“…Therefore, successful strategies targeting the role of glutamate in cancers have focused on restricting glutamine metabolism via glutaminase inhibition (132). Studies investigating the noncompetitive allosteric GLS1 inhibitor CB-839 have demonstrated that blocking glutamine metabolism has anticancer activity against triple-negative breast cancer, lung adenocarcinoma, chondrosarcoma, lymphomas, esophageal squamous cell carcinoma, and hepatocellular carcinoma (132)(133)(134)(135)(136)(137)(138). Currently, there are 12 ongoing clinical trials evaluating the CB-839 in patients with colorectal cancer (NCT02861300 and NCT03263429), myelodysplastic syndrome (NCT03047993), advanced stage non-small cell lung cancer (NCT04250545 and NCT03831932), diffuse astrocytoma (NCT03528642), ovarian cancer (NCT03944902), refractory multiple myeloma (NCT03798678), advanced or metastatic solid tumors ( N C T 0 3 9 6 5 8 4 5 ) , m e t a s t a t i c r e n a l c e l l c a r c i n o m a (NCT03428217), malignancies with NF1, KEAP1/NRF2, or STK11/LKB1 mutations (NCT03872427), and non-squamous non-small-cell lung cancer (NCT04265534).…”
Section: Restriction Of Glutamate or Glutamine Metabolism Via Inhibitors Of Glutaminase Are Effective Against Myelodysplastic Syndromementioning
confidence: 99%
“…DON is a glutamine antagonist that has been shown to inhibit the activity of GLS, but it also has other enzymatic targets, such as those involved in nucleotide and asparagine synthesis (Ahluwalia et al, 1990 ; Lemberg et al, 2018 ; Rosenbluth et al, 1976 ). CB‐839 is a highly selective inhibitor of GLS and is currently in clinical trials for treating several cancer types in combination with other therapeutics (Jin et al, 2020 ; Zhao et al, 2020 ). In the current study, culture with DON or CB‐839 decreased development to the blastocyst stage, and culture with DON decreased total cell number in the blastocyst‐stage embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, among various options, glutaminolysis-dependency or extensive use of autophagy may provide attractive targets. In recent years, various drug candidates targeting metabolism, some of which are likely relevant for CSC, have entered clinical investigation, including autophagy activators (e.g., metformin, alisertib) [ 126 ], PDK inhibitors [ 159 ], glutamine transporter inhibitors and glutaminase inhibitors (e.g., telaglenastat) [ 61 , 160 , 161 ], FA synthase inhibitors [ 162 , 163 ], P53 activators [ 164 , 165 ], and β-adrenergic receptor antagonists [ 166 , 167 ]. Further studies are warranted to determine the efficacy of these drugs in combination with standard care chemotherapies or synthetic lethal approaches in cancers with unmet needs.…”
Section: Conclusion/perspectivesmentioning
confidence: 99%